Digital environments of learning in distance education for the initial education of teachers: perceptions about their relevance - Ñáñez-Rodríguez, José Julián; Solano-Guerrero, Juan Carlos; Bernal-Castillo, Edwin (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This document looks at the perception of teachers and students on the implementation of Information and Communication Technologies, ICT, together with the experience of the pedagogical portfolios, in degree programs of Colombian universities. The work had a qualitative, exploratory and correlational approach, of the action research type. The sample consisted of 77 teachers and 192 students, from the Universidad del Tolima. Students have a positive attitude towards ICT, which is strongly correlated with their expertise in these technologies. The use of ICT by teachers is diminished to the extent that they give more relevance to face-to-face work, according to the students' perception. The students' perception was positive with respect to the pedagogical portfolio, considering it as a tool that contributes to formation and autonomous learning, two essential aspects of distance education. It is concluded that the educative processes transcend the instructional and training exercises, while they seek a transformation of the subject, which transcends the logic of procedural execution.